(3TQM CHfjI GdCaYGd dGHf eGdcs - (3eMeO Hf YeQ GHf ejGQg Hf YHO Gddg GdaGSjs; (3CHh YHO Gddg HOQ GdOjf eMeO Hf eMeO Hf YHO Gddg Hf eGdc GdWGFj , GHf GdfGXe,J (B686 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMejO GdeLjO GdeHOF GdeYjO hHYO aEfj cfJ TQMJ GdbUjOI GddGejI GdeSeGI CHfjI GdGaYdG aj Yde GdUQa ddYGde LeGd GdOjf Hf eGdc s
(3BNQgG (B:s
(3hGdCKhGH LeY KhH hgh SJYGQI gfG hGdSJQ HcSQ GdSjf hGdKhH GdSGJQ s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B239 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B135s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs